Implementasi Model Discovery Learning Pada Pembelajaran Sejarah Kebudayaan Islam - Lestari, Ayu; Muliati, Indah (An-Nuha, 2023)
This research aims find out how to plan, implement and evaluate the Discovery Learning model in Islamic Cultural History in VIII D grade. This research uses qulitative methods with a case study approach, the data of this research is obtained through direct interviews with three informants (deputy curriculum, teacher of Islamic Cultural History, and four students). To corroborate the interview data, the author conducted observation activities by being directly involved in the process of learning activities in the classroom. Data analysis techniques use data reduction, data presentation, and the conclusion. The results showed the implementation of the Discovery Learning in Islamic Cultural History lessons at MTsN 02 Empat Lawang includes: providing stimulation to students, identifying problems, collecting data, processing data, proving and conclusions. The conclusions of the implementation of the Discovery Learning in Islamic Cultural History lessons at MTsN 02 Empat Lawang is carried out with several steps. First, the teacher ask students to convey the results of the discussion. Second, the teachers ask students to makes important notes from the results of the discussion. Third, the students collects the results of the discussion to the teacher. And last, the teacher gives assignments in the form of written test as evaluation material.